Fabrication of Single Phase Barium Stannate (BaSnO3) Thin Film for Methane Sensing. (2019) - Anchal, Brij Bansh Nath; Singh, Preetam; Pyare, Ram
Abstract: Development of thin film sensor with high activity and selectivity especially for methane is important in order to secure the life of labourers working in coal fields/mines. Bariums Stannate (BaSnO3 ) based thin film sensor are developed by sol gel route for the methane sensing. The development of thin films were characterized by X-ray diffractions, HR-SEM, EDX, AFM and testing of sensing was carried out in the temperature range of 100°C to 200°C for 100 to 400 ppm of methane gas concentration. Highest activity of the BaSnO3 films was observed for 400 ppm concentration of methane at 200 o C.